Analysis of Swearing Words in Movie Birds of Prey (And The Fantabulous Emancipation of One Harley Quinn) - Andika, Sansahmal Ari; Setyawan, Agustinus Hary (Peneliti.net, 2024)
In social interaction, humans use language as a medium of communication; in the development of language, the phenomenon of swear words occurs in social interaction. Swear words are included in abusive words and have negative tendencies in their use, but swear words can have different interpretations if used in specific contexts. This study analyzes the type and motive of swear words used by the characters in Birds of Prey (and Fantabulous Emancipation of One Harley Quinn). This research uses a qualitative method, Anderson and Trudgill's (1990) theory to analyze the types, and Anderson's theory in Kajalainen's (2002). In this study, swear words were found, namely, 1Fucking/Fuck, 2Mother Fucker, 3Shit, 4Bitch, 5Ass/Asshole, 6Jesus Christ/Christ, 7Dick, 8Slut and 9Damn.The four types are Expletive Swearing, Abusive Swearing, Humorous Swearing, and Auxiliary Swearing. It also includes three motives: Psychological Motive, Social Motive, and Linguistic Motive.